ANALISIS ANCAMAN KEAMANAN JARINGAN SERTA IMPLEMENTASI FIREWALL, IDS, DAN IPS DALAM MENINGKATKAN PERLINDUNGAN SISTEM PADA LINGKUNGAN JARINGAN KOMPUTER - Sophia Widiana; Sri Ayu Kartika; Reni Try Setianingsih; Reyna Aulia Zavira; Anita Sindar (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2026)
The development of information technology has increased the use of computer networks in various sectors, including educational settings. However, this increased network usage has also been accompanied by an increase in cybersecurity threats that can disrupt service availability and data security. One frequently encountered threat is a Distributed Denial of Service (DDoS) attack, which can degrade network performance and disrupt academic activities. This study aims to analyze network security threats and the implementation of firewalls, Intrusion Detection Systems (IDS), and Intrusion Prevention Systems (IPS) to improve system protection in computer network environments. The method used is a literature review with a qualitative descriptive approach through an analysis of several studies discussing DDoS attacks in educational environments. The results indicate that DDoS attacks can degrade the quality of network services and hinder user access to academic systems. Furthermore, the implementation of firewalls, IDS, and IPS has been proven to improve network security through more effective filtering, detection, and prevention of attacks. Based on the analysis, implementing layered security that combines firewalls, IDS, and IPS can be an effective solution for improving system protection and maintaining the stability of computer network services.